Increasing the content of fiber and minerals in gnocchi with added dragon fruit peels as sub stitution of ingredient for improvement of food product quality and human health - L. Rahmah; Arif N. M. Ansori; Novi I. P. Sari (Пищевые системы, 2024)
Gnocchi is a type of homemade pasta made from potatoes, flour and eggs. Improving food product quality in terms of nutrition in gnocchi products it is possible now also use food waste. In addition to improvement of food product quality and human health, the addition of dragon fruit peel, which is considered as waste, can provide reasonable solutions or ideas about recycling of food waste. In this study, the produced food product was gnocchi with addition of by-product — dragon fruit peel, which was tested for fiber content and content of the following minerals: iron, potassium, calcium. The data obtained were then analyzed statistically by the SPSS program to determine the effect of variation using the T-test. Based on the results of the study it was concluded that the content of dietary fiber of dragon fruit peel in the sample of gnocchi denoted as F3 featured the highest water-soluble dietary fiber content with a score of 1.33%, water insoluble dietary fiber content with a score of 1.86%. and total dietary fiber content with a score of 3.19%. This also shows that the more dragon fruit peel is added, the higher is the total dietary fiber content in gnocchi with addition of dragon fruit peel. This high dietary fiber will be beneficial to humans, especially good for the digestive system. Meanwhile, the mineral content of gnocchi with dragon fruit peel also showed that the F3 sample had the highest mineral content, in particular — iron (Fe) in amount of 1.886 mg/100 g, potassium (K) 6.179 mg/100 g, and calcium (Ca) in amount of 25.339 mg/100 g. This also shows that the addition of dragon fruit peel is useful for improvement of human health and the quality of food product, i. e. gnocchi by increasing the total content of dietary fiber and improving the mineral composition of gnocchi due to addition of dragon fruit peel.